Mechanisms for Suppression of Interleukin-6 Expression in Peritoneal Macrophages from Docosahexaenoic Acid-Fed Mice - Shi, Yuhui (2008)
Consumption of the trichothecene mycotoxin deoxynivalenol (DON) induces interleukin-6 (IL-6)-dependent IgA nephropathy (IgAN) in mice. This effect can be prevented by feeding long chain n-3 polyunsaturated fatty acids (PUFAs) found in fish oil. The purpose of this study was to identify the signal transduction pathways by which DON upregulates IL-6 in the peritoneal macrophage and how consumption of fish oil enriched with the n-3 PUFA, docosahexaenoic acid (DHA), suppresses these processes. Incubation with DON induced IL-6 expression in naïve macrophages maximally at 3 h. Knockdown of the transcription factor cAMP response element-binding protein (CREB) or pharmacologic inhibition of the CREB kinases, Akt1/2, MSK1 and RSK1, downregulated this expression. Inhibition of double-stranded RNA-activated protein kinase (PKR) suppressed not only IL-6 expression but also phosphorylation of CREB and its upstream kinases, Akt1, MSK1 and RSK1. Phosphorylations of PKR, CREB kinases and CREB were markedly impaired in peritoneal macrophages isolated from mice that consumed DHA-enriched fish oil for 6 to 8 wk. DHA’s effects were not explainable by increased activity of protein phosphatase 1 and 2A since both were suppressed in mice consuming the DHA diet. Although cells cultured directly with DHA expressed less IL-6 compared to cells cultured with arachidonic acid (AA), neither fatty acid treatment affected DON-induced protein phosphorylation. Furthermore, DHA and AA similarly inhibited cell-free protein kinase activity. These data suggest that DON-induced IL-6 expression is CREB-mediated and PKR-dependent and that requisite kinase activities for these pathways were suppressed in macrophages from mice fed DHA for an extended period.